Gambaran Amplitudo Akomodasi Pada Pasien Kelainan Refraksi di Rumah Sakit Mata Makassar Tahun 2024 - Alfia Abbas; Andi Senggeng Relle; Hasnawati S (RS Mata Makassar, 2025)
The amplitude of accommodation (AA) reflects the eye’s ability to adjust its refractive power to focus on near objects and is influenced by age, sex, and refractive status. This descriptive observational study aimed to evaluate the amplitude of accommodation among patients with refractive errors at Makassar Eye Hospital in 2024. A total of 100 participants aged 20–68 years were selected using purposive sampling, resulting in 200 eyes examined. AA was measured monocularly using the push-up method with a Royal Air Force (RAF) Rule, and calculated using the formula AA = 100/NPA (in cm). The overall mean AA was 7.0 ± 0.01 diopters (D). Higher mean AA values were found in the 28–36 age group (9.3 ± 0.06 D) and in female patients (7.4 ± 0.00 D), while the lowest AA was observed in hyperopic individuals (5.7 ± 0.39 D). These findings indicate that AA varies across age groups, sexes, and refractive types, and underscore the need for accommodative function evaluation as part of routine refractive assessments in optometric practice.